2010
DOI: 10.1103/physrevlett.105.243002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of the Magnetic Quadrupole Contribution to the Lyman-α1Transition in a Hydrogenlike Ion

Abstract: We report the observation of an interference between the electric dipole (E1) and the magnetic quadrupole (M2) amplitudes for the linear polarization of the Ly-α1 (2p3/2→1s1/2) radiation of hydrogenlike uranium. This multipole mixing arises from the coupling of the ion to different multipole components of the radiation field. Our observation indicates a significant depolarization of the Ly-α1 radiation due to the E1-M2 amplitude mixing. It proves that a combined measurement of the linear polarization and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 23 publications
(45 reference statements)
2
45
0
Order By: Relevance
“…However, to the best of our knowledge, there are few work about the linear polarization of tungsten X-ray emissions in ITER fusion plasmas. Since angle-resolved observables, such as linear polarization and angular distribution, are much more sensitive to various atomic effects and physical variables than the total (angle-averaged) decay rates of X-ray emissions, the angle-resolved studies of X-rays have been used to extract a variety of physical effects in the last few decades [30][31][32][33][34][35][36]. For those strong X-ray emissions from tungsten ions, they are hardly affected by the radiative damping caused by additional atomic excitation processes [27] and, thus, are relatively clean atomic radiations, which could be used to study the angle-resolved observables to reveal the population mechanism of excited levels [37,38] and perhaps to reflect plasma conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there are few work about the linear polarization of tungsten X-ray emissions in ITER fusion plasmas. Since angle-resolved observables, such as linear polarization and angular distribution, are much more sensitive to various atomic effects and physical variables than the total (angle-averaged) decay rates of X-ray emissions, the angle-resolved studies of X-rays have been used to extract a variety of physical effects in the last few decades [30][31][32][33][34][35][36]. For those strong X-ray emissions from tungsten ions, they are hardly affected by the radiative damping caused by additional atomic excitation processes [27] and, thus, are relatively clean atomic radiations, which could be used to study the angle-resolved observables to reveal the population mechanism of excited levels [37,38] and perhaps to reflect plasma conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the x rays produced by the decay of individual magnetic sublevels are polarized differently, the measured degree of polarization probes the distribution of am [ 13,[49][50][51]. Although in some cases the polarization effects beyond the dipole approximation are important [26], for the sake of clarity we limit the discussion to the leading electricdipole approximation, which is adequate for the experimental accuracy of the present work. It can be shown that the degree of polarization is P(J = 1) = 3o;2(cro -e g ) V 2 + a 2(ob -o"i) P(J = 3/2) = , 3" 2(7 /2 °V2) , (2) in [15] and Eq.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, a number of experiments that measured the DR cross sections using electron beam ion traps (EBITs) had observed the DR x rays perpendicularly to the electron beam propagation direction [19][20][21][22][23][24][25], The interpretation of such experiments requires knowledge of the DR x-ray anisotropy and, thus, of its polarization. Furthermore, measurements of the x-ray emission anisotropy and polarization can comple ment each other to access effects beyond the electric-dipole approximation [26].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the total intensity of individual x-ray lines, angle-and polarizationresolved measurements have typically been found much more sensitive with regard to small (inner-) atomic interactions, such as the hyperfine structure [1,2], the Breit interaction [3,4,5], or the mixing of different multipoles of the radiation fields [6,7,8]. Until the present, however, the vast majority of such angle-and polarization-resolved studies were made for sufficiently well-isolated fine-structure levels, while little attention was paid so far to photon cascades via overlapping resonances.…”
Section: Introductionmentioning
confidence: 99%